Effects of resistance and speed on electromyographic activity of thigh and gluteal muscles in elite athletes throughout resisted sprint running - Macchi, R.; Hegyi, A.; Giroux, C.; Rabita, G.; Nordez, A.; Hollville, E.; Couturier, A.; Fornasier-Santos, C.; Slawinski, J.; Morin, J. B.; Lacourpaille, L.; Guilhem, G. (Medicine & Science in Sports & Exercise, 2025)
Purpose The application of horizontal resistance is key in sprint training to modulate velocity and promote adaptations. However, the interaction between velocity and resistance on muscle excitation remains insufficiently studied. This study assessed the electromyographic (EMG) activity of thigh and gluteal muscles in response to varying velocity and resistance during sprinting.